The 2016-Income Tax Reforms of Ethiopia: Drivers, Major Legislative Changes, and Constraints - Silesh, Gizachew; Yemata, Belete Addis; Beza, Misganaw Gashaw; Akalu, Mulugeta; Asegid, Zerihun (Bahir Dar University Journal of Law, 2023)
This article investigated Ethiopia’s 2016 income tax reform in terms of its drivers, actors involved in the process, major legislative changes and constraints that may impede its intended goals. It employed a qualitative research methodology, by which it gathered relevant data from key informant interviews, and document review. Legal analysis and description of issues are used as methods of analysis and discussion of the findings. The article identified the drivers of the reforms as addressing changes in the economy, enhancing revenue mobilization, improving efficiency and equity, and addressing gaps in previous income tax legislations. In the reform process, the Ministry of Finance had the upper hand position, though; practically the International Monetary Fund had a significant stump in the course of the process. However, the participation of other key national actors, including the Ministry of Revenues and the Ethiopian Chamber of Commerce was minimal. The reform has introduced major legislative changes, including the introduction of Schedule ‘E’ and new tax bases; taxation of residual income; and consolidation of tax administration laws. The article also discussed constraints that may impede the goals of the reforms, including the absence of impact assessment of the 2016 reforms; inflation; poor tax administration; lack of meaningful stakeholder participation; and low tax-to-GDP ratio. Finally, suggestions are made for undertaking impact assessment of the 2016 income tax reforms; redesigning the income tax system to be responsive to inflation; modernizing the tax administration; and enhancing meaningful stakeholders’ participation.